Conservative laparoscopic approach to paratubal cyst torsion in young girls: three cases of preserved fertility - Dubey, Khushbu; Choudhury, Satish; Gedam, Prachi; Mangani, Deepika; Gupta, Avantika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Paraovarian and paratubal cysts, constituting approximately 10% of all adnexal masses, are typically benign and originate from the mesothelial lining or remnants of the Müllerian and Wolffian ducts. Although the incidence of torsion is lower in paraovarian cysts compared to ovarian cysts, it presents notable challenges, particularly in young women where fertility preservation is crucial. This report discusses three cases of torsed paratubal cysts successfully managed through laparoscopic techniques designed to prioritize fertility preservation. The surgical approach emphasized careful detorsion, aspiration of cyst contents for ease of manipulation, and the avoidance of energy devices during dissection to maintain vascular integrity in the ovaries and fallopian tubes. A strategic incision placed away from the fallopian tube further minimized the risk of injury, thereby safeguarding reproductive potential. Postoperative outcomes demonstrated effective pain relief, with histopathological findings of serous cystadenoma underscoring the importance of meticulous surgical techniques in preserving reproductive function in young patients.